And the risen bread selected poems, 1957 - 1997 - Berrigan, Daniel 1921-2016 (Fordham Univ. Press, 1998)
And the Risen Bread is a harvest of forty years of poetry by Daniel Berrigan. Beginning with poems written largely on biblical themes, the book moves on to reflect the increasingly experiential inspiration of Berrigan's poetry - poems written from the front lines of the struggle for peace and justice, poems from the courtroom and the prison cell, and finally, poems of harsh but hopeful reflection.
Keywords: Geschichte 1900-2000; American poetry -- Catholic authors; American poetry -- 20th century; Christian poetry